Proceedings of the International Conference on Mathematical Sciences and Statistics 2022 (ICMSS 2022) 2022
DOI: 10.2991/978-94-6463-014-5_41
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Flow of Casson Fluid with Carbon Nanotubes Past an Accelerated Disk

Abstract: In this study, the impact of heat transfer on free convective Casson nanofluid flow induced by an accelerated disk is analyzed. The study of non-Newtonian Casson nanofluid that is suspended by single wall carbon nanotubes (SWCNTs) and multi wall carbon nanotubes (MWCNTs) has a vital role in human blood flows. The problem is governed by governing momentum and energy equations that come along with appropriate conditions for initial and accelerated boundary. The dimensionless form of the governing equation is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The study found that the Grashof number has improved the velocity field and lowered the momentum boundary layer thickness. The study on free convection was rapidly established by considering the different problems and situations by Hamdan et al (2020) and Mohamad et al (2022). They found that the Grashof number has a significant impact on the velocity and momentum boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the Grashof number has improved the velocity field and lowered the momentum boundary layer thickness. The study on free convection was rapidly established by considering the different problems and situations by Hamdan et al (2020) and Mohamad et al (2022). They found that the Grashof number has a significant impact on the velocity and momentum boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Aman et al, [17] investigated the presence of MHD on the unsteady flow and founds that an increases values Casson parameter, the velocity is increase while velocity is decrease when magnetic parameter is increases. There have been several investigations into the MHD effect in different problems and found that MHD effect have an important impact on the boundary layer flow [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%